Training on Cultivation and Production of Manila Duck in a Venture Group of RT. 12, RW. 01 Sukamerindu Village, Bengkulu City - Sugianto, Nanang; Refrizon, Refrizon; Dani, Muhammad (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The procurement of Day Old Duck of manila or better known as manila duck seeds is a major problem experienced by joint venture groups owned by RT residents. 12, RW. 01 Kelurahan Sukamerindu (partner) has just started operating and has a limited budget. The production of the partner's manila ducklings is carried out conventionally and is considered very slow and has only 50% hatching success. The use of an egg incubator (incubator egg machine) is considered to be an alternative solution for solving problems experienced by partners. However, the limited knowledge, skills, and experience of group members caused the alternative solution to be delayed. Therefore, the partners asked the service team to provide education, training, practice, and assistance in poultry farming and the application of egg incubators to optimize and accelerate the production of manila duck seeds. The method that will be applied is to provide learning, training, and mentoring with a theoretical and practical approach that includes the basics of poultry farming (Manila ducks), management and care of manila ducks (feed, housing and prevention and overcoming diseases in manila ducks), basics and use of egg incubator and simple egg incubator making. The pre-test and post-test results illustrate that partners have understood the technique of selecting eggs for the hatching process, operating and maintenance techniques for fully automatic egg incubators, and maintenance techniques ranging from DOD to adult manila ducks. The target audience is also equipped with techniques for maintaining ideal cage conditions, main feed, and alternative feed for manila ducks. The mentoring process by the service team continues to be carried out so that the optimization of manila duck production for this joint venture group can be achieved properly.